Criminal liability for abuse according to the law of Ukraine - Лихова, Софія Яківна; Бойко, Віталій Ігорович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article defines criminal liability for abuse in criminal legislation of Ukraine. Authors consider a special subject of a crime– the official, a law enforcement officer. In conclusion, it is noted that law enforcement officers can commit any crime against a person and all these acts of violence on their part (the cases of both physical and mental abuse) are covered by the concept of «abuse of powers or official authority». This approach of jurisprudence is imperfect and does not contribute to the protection of the rights and legitimate interests of citizens from the arbitrariness of law enforcement officers. The right ща freedom from tortures and inhuman or degrading treatment or punishment is the peremptory norm of the international law. According to the provisions of the core international human rights documents such as the Convention for the Protection of Human Rights and Fundamental Freedoms, the International Covenant on Civil and Political Rights and the others no exceptions to this fundamental human right are allowed. Some important state obligations are derived from this right, including the obligation to refrain from the acts of torture and inhuman or degrading treatment or punishment and prevent them, as well as the obligation to conduct effective investigations and actions to bring the guilty persons to justice in the courts. This research, taking into account the relevance of this subject, is dedicated to one of the most important aspects of this complex problem - the analysis of the norms of the Criminal Code of Ukraine that establishes liability for abuse. The state criminal legislation of Ukraine contains adequate provisions that concern acts of abuse. The general norm that protects a person from torture and other atrocities is contained in article 28 of the Constitution of Ukraine that states that "no one shall be subjected to torture or to cruel, inhuman or degrading treatment or punishment." The guarantee compliance with this constitutional process is, in particular, a number of criminal law provisions contained in the different sections of the Special Part of the Criminal Code of Ukraine. But the fact that there is a great number of these norms and they duplicate each other, creates certain problems in their application.